AKTIVITAS PEMETIK KOPI DALAM SENI LUKIS - JEMI KARDILA, Drs. Erfahmi,M.Sn, Yasrul Sami, S.Sn., M.Sn (Serupa The Journal of Art Education, 2015)
The purpose of the creation of this thesis to visualize the activity of coffee pickers in contemporary realist painting. The ten works are completed to the fullest have represented the themes raised. The ten works are: 1) Departing, 2) Chain Ban, 3) Grazing and gleaning, 4) Waiting Red, 5) Still Bit, 6) Too Heavy, 7) Exchange of Information, 8) Drying Coffee, 9) Green and red, 10) Wet milling. Tenth these works provide an overview of the process of the activities of the coffee pickers who have worked so hard for the sake of taking daily wages earned but not in accordance with the minimum wage should be.Keywords: coffee pickers activity, realist painting, contemporary.